Could SARS-CoV-2 herald a surge of multiple sclerosis? - Shalaby, Nevin Mohieldin (Egypt J Neurol Psychiatr Neurosurg, 2021)
During the current COVID-19 pandemic, many queries are raised regarding its nature, outcome, and sequelae. This letter raises the concern of potential impact on increasing the incidence of multiple sclerosis whose pathology involves a possible viral etiology. Besides, the potential neurotropism of the acute respiratory distress syndrome corona virus-2 (SARS-CoV-2), which is still not established, may raise concerns about the use of certain disease modifying therapies namely natalizumab.